Opioid prescribing exceeds consumption following common surgical oncology procedures. Issue 1 (30th October 2020) - Eyrich, Nicholas W.; Sloss, Kenneth R.; Howard, Ryan A.; Klueh, Michael P.; Englesbe, Michael J.; Waljee, Jennifer F.; Brummett, Chad M.; Sabel, Michael S.; Dossett, Lesly A.; Lee, Jay S.
Abstract: Background and Objectives: Surgical oncology patients are vulnerable to persistent opioid use. As such, we aim to compare opioid prescribing to opioid consumption for common surgical oncology procedures. Methods: We prospectively identified patients undergoing common surgical oncology procedures at a single academic institution (August 2017–March 2018). Patients were contacted by telephone within 6 months of surgery and asked to report their opioid consumption and describe their discharge instructions and opioid handling practices. Results: Of the 439 patients who were approached via telephone, 270 completed at least one survey portion. The median quantity of opioid prescribed was significantly larger than consumed following breast biopsy (5 vs. 2 tablets of 5 mg oxycodone, p  < .001), lumpectomy (10 vs. 2 tablets of 5 mg oxycodone, p  < .001), and mastectomy or wide local excision (20 tablets vs. 2 tablets of 5 mg oxycodone, p  < .001). The majority of patients reported receiving education on taking opioids, but only 27% received instructions on proper disposal; 82% of prescriptions filled resulted in unused opioids, and only 11% of these patients safely disposed of them. Conclusions: This study demonstrates that opioid prescribing exceeds consumption following common surgical oncology procedures, indicating the potential for reductions in prescribing.